Numerical modelling of the mechanical behaviour of rubbercrete. (1st January 2021) - Gregori, Amedeo; Castoro, Chiara; Mercuri, Micaela; Angiolilli, Michele
Highlights: Numerical models were developed to describe the rubbercrete mechanical behaviour. Compressive strength and elastic modulus were investigated. Equations are provided. Sensitivity analyses on mechanical properties of rubbercrete were performed. Numerical models are sensitive to the input properties assumed in the models. Numerical analyses well reproduced experimental data, representing a complementary tool for design procedures. Abstract: Several finite element models have been analysed to numerically investigate the effects on the compressive strength and on the elastic modulus of a concrete with partial replacement of natural aggregates with different amounts and types of rubber particles from waste tyres. Percentages of substitution from 0% to 83% have been considered with rubber particles size ranging from 3 mm to 30 mm. Analytical relationships have been proposed to analyse the reduction factor of the compressive strength (SRF) and the reduction factor of the elastic modulus (ERF) of this material, known as rubbercrete. Results are confirmed similar to those from experimental campaigns reported in the literature. Results from the reference compressive strength variation are confirmed to depend on the size of the rubber particles, regardless the amount. A sensitivity analysis has been also carried out on the elastic modulus of the rubber and rubbercrete final properties are demonstrated not to clearly depend on it.